Editorial - Maria de Nazaré de Oliveira Fraga (Rev Rene)
The publication of this number Rev. RENE materializes effort and celebration. The effort comes great responsibility account crediting to this journal that was born under the inspiration of creating and maintaining more a publishing space of knowledge about nursing and health produced in Brazil. As a new journal, this specialized communication vehicle faces significant challenges already addressed in the editorial of our previous number: shortage of financial support and low subscriber numbers, small demand for articles that undergo evaluation for publication, a certain inbreeding in order, Moreover, the predominance of articles from the own academic unit that hosts the journal.